2017
DOI: 10.1007/s00256-017-2742-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance cinematography of the fingers: a 3.0 Tesla feasibility study with comparison of incremental and continuous dynamic protocols

Abstract: MRCF is feasible with appropriate image quality during continuous motion using a finger-gating device. Almost perfect image quality is achievable with incremental PD imaging, which represents a compromise for MRCF with the drawback of prolonged scanning time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Bayer et al found a better image quality with an optimized bSSFP sequence compared to spoiled-GRE sequence for real-time dynamic MRI of finger motion at 3.0 T based on subjective evaluation. But they also reported a reduced temporal resolution of 1–3.6 s and more susceptibility artifacts on the bSSFP sequence (20). On the other hand, Shaw et al found that the RF-spoiled sequence was more robust than the bSSFP sequence for real-time dynamic MRI of the wrist at 3.0 T because it was less affected by artifacts (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bayer et al found a better image quality with an optimized bSSFP sequence compared to spoiled-GRE sequence for real-time dynamic MRI of finger motion at 3.0 T based on subjective evaluation. But they also reported a reduced temporal resolution of 1–3.6 s and more susceptibility artifacts on the bSSFP sequence (20). On the other hand, Shaw et al found that the RF-spoiled sequence was more robust than the bSSFP sequence for real-time dynamic MRI of the wrist at 3.0 T because it was less affected by artifacts (26).…”
Section: Discussionmentioning
confidence: 99%
“…Grading scales or elements related to a disease (for example, presence or absence of the pathology, number of lesions, etc.) can be used for a subjective evaluation (17,20). Objective metrics are typically done in comparison with a reference image, like SNR, CNR, Shannon's information content, or root-mean-square error for MRI (16).…”
Section: Discussionmentioning
confidence: 99%
“…Another dynamic sequence analysed in our study was TRUFI, which is characterised by the highest image to time ratio, 60 scans per 22 seconds. Previous studies demonstrated high effectiveness of this sequence in dynamic imaging of hand movements, albeit with a 3.0T scanner [17]. The slices obtained with this sequence accurately depict even subtle changes in fast-moving anatomical structures.…”
Section: Discussionmentioning
confidence: 88%
“…The distal situation of these joints makes it possible to use a "rigid" RF coil. Bayer et al performed dynamic MRI sequences of the finger with a sky boot-shaped coil [63], whereas Schellhammer and Vantorre used a knee coil to study finger motion [52]. The hand can also be positioned within a head coil to investigate all degrees of freedom ( Fig.…”
Section: Distal Jointsmentioning
confidence: 99%